Analisis Perbedaan Tax Amnesty Jilid Pertama Dengan Program Pengungkapan Sukarela (PPS) - Taufik, Haviz; Efris Saputri, Eka Julianti; Fitra Apriandi, Rian; Pradana, Aditya (Jurnal Akuntansi & Keuangan Unja, 2024)
This research analyzes the differences between tax amnesty and the voluntary disclosure program (PPS). The research method focuses on descriptive qualitative research. Where the research results show that state revenue from PPS is more optimal and effective than tax amnesty. This was caused firstly, at the time of the implementation of the tax amnesty, Law No. 9 of 2017 concerning Stipulation of Government Regulations in Lieu of Law No. 1 of 2017 concerning Access to Financial Information for Tax Purposes had not yet been passed. This was certainly difficult for the Director General. taxes to gain access to taxpayer information from existing stakeholders so that the data obtained is limited and makes the implementation of the tax amnesty not optimal. Meanwhile, when the PPS Law was implemented, it made it easier for the Director General of Taxes to access information relating to taxpayers' tax obligations so that with more data, state revenues from PPS were also greater and maximized; Tax amnesty has a smaller tax rate compared to PPS and the size of the rate depends on which period the taxpayer wants to participate in. Meanwhile, PPS divides tax rates not based on period but based on policy I and policy II as well as the type of asset disclosure.